2021
DOI: 10.1007/s10853-021-05929-8
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanics of the small punch test: a review and qualification of additive manufacturing materials

Abstract: The small punch test (SPT) was developed for situations where source material is scarce, costly or otherwise difficult to acquire, and has been used for assessing components with variable, location-dependent material properties. Although lacking standardization, the SPT has been employed to assess material properties and verified using traditional testing. Several methods exist for equating SPT results with traditional stress–strain data. There are, however, areas of weakness, such as fracture and fatigue appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 188 publications
(366 reference statements)
0
23
0
Order By: Relevance
“…The two commonly used methods are numerical simulation and the empirical correlation method. In this paper, the second method is used to correlate the characteristic data on the original load-deflection curves with the conventional test results to evaluate the changes in the tensile properties and fracture properties [22,23].…”
Section: Small Punch Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The two commonly used methods are numerical simulation and the empirical correlation method. In this paper, the second method is used to correlate the characteristic data on the original load-deflection curves with the conventional test results to evaluate the changes in the tensile properties and fracture properties [22,23].…”
Section: Small Punch Testmentioning
confidence: 99%
“…The ultimate tensile strength can reflect the changes in the tensile properties of the material. Studies have shown that the ultimate tensile strength can be estimated from two characteristic data, which are P max the maximum load, and P i the load corresponding to the deflection of 1.1 times sample thickness [22,23]. The corresponding empirical correlations have been derived to analyze the irradiation effect caused by ion and neutron irradiation for some specific materials [20].…”
Section: Small Punch Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The test setup consists of a die with upper and lower parts to fix the position of the specimen and a punch with a spherical tip to penetrate the specimen under constant speed. Recently, SPT has been widely used to estimate the mechanical properties of metallic and nonmetallic materials, especially when there is no excess of materials [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For assessing mechanical and fracture properties, a variety of correlations have been found between standard testing and SPT data. As these correlations are based on a specific set of materials [1][2][3][4][5] and testing methods, they must be reviewed for their validity and reliability. In the absence of an initial crack in SPT specimens, the application of these correlations to predict material fracture characteristics is unreliable.…”
Section: Introductionmentioning
confidence: 99%